A Generic Open-Loop Algorithm for Three-Phase Grid Voltage/Current Synchronization With Particular Reference to Phase, Frequency, and Amplitude Estimation - Freijedo, F.D.; Doval-Gandoy, J.; Lopez, O.; Acha, E. (IEEE transactions on power electronics, 2009)
This paper presents a new open-loop architecture for three-phase grid synchronization based on moving average and predictive filters, where accurate measurements of phase, frequency, and amplitude are carried out in real time. Previous works establish that the fundamental positive sequence vector of a set of utility voltage/current vectors can be decoupled using Park's transformation and low-pass filters. However, the filtering process introduces delays that impair the system performance. More specifically, when the input signal frequency is shifted above the nominal, a nonzero average steady-state phase error appears in the measurements. To overcome such limitations, a suitable combination of predictive and moving average finite impulse response (FIR) filters is used by the authors to achieve a robust synchronization system for all input frequencies. Moving average filters are linear phase FIR filters that have a constant time delay at low frequencies, a characteristic that is exploited to good effect to design a predictive filter that compensates such time delays, enabling zero steady-state phase errors for shifted input frequencies. In summary, the main attributes of the new system are its good frequency adaptation, good filtering/transient response tradeoff, and the fact that its dynamics is independent of the input vector amplitude. Comprehensive experimental results validate the theoretical approach and the high performance of the proposed synchronization algorithm.